Qur'anic Recitation Etiquette Based on Hadith: Contribution to Contemporary Islamic Education and Qur'anic Literacy - Abdul Halim; Budiman Muhammad Nur; Jajat Sudrajat (Al-Fikru: Jurnal Ilmiah, 2026)
This study aims to identify themes in hadith regarding the etiquette of reading the Qur’an, analyze the ethical, spiritual, and pedagogical dimensions contained therein, and explain their contribution to contemporary Islamic education and Qur’anic literacy. This study is motivated by a trend in Qur’anic education that places greater emphasis on the technical aspects of recitation rather than on strengthening ethical and spiritual values. The research employs a thematic literature review method using a qualitative approach. Primary data sources consist of hadiths contained in authoritative hadith collections, while secondary sources are drawn from relevant scholarly articles and academic literature. The data were analyzed through a process of coding, categorization, and thematic synthesis. The results revealed four main themes: spiritual and physical preparation before recitation; engagement of the heart through tadabbur; recitation in a measured and balanced manner; and respect for the Qur’an in both personal and social contexts. These findings affirm that the etiquette of reciting the Qur’an based on hadith contributes to the strengthening of spiritual character, the development of reflective Qur’anic literacy, and the formation of a holistic and transformative Islamic pedagogy.